Racial Assumptions Color the Mental Representation of Social Class - Lei, Ryan F.; Bodenhausen, Galen V. (Frontiers in Psychology, 2017)
We investigated the racial content of perceivers’ mental images of different socioeconomic categories. We selected participants who were either high or low in prejudice toward the poor. These participants saw 400 pairs of visually noisy face images. Depending on condition, participants chose the face that looked like a poor person, a middle-income person, or a rich person. We averaged the faces selected to create composite images of each social class. A second group of participants rated the stereotypical Blackness of these images. They also rated the face images on a variety of psychological traits. Participants high in economic prejudice produced strongly class-differentiated mental images. They imagined the poor to be Blacker than middle-income and wealthy people. They also imagined them to have less positive psychological characteristics. Participants low in economic prejudice also possessed images of the wealthy that were relatively White, but they represented poor and middle-class people in a less racially differentiated way. We discuss implications for understanding the intersections of race and class in social perception.